El género Juncus L. (Juncaceae) en Andalucía (España): datos sobre la distribución regional de sus especies. The genus Juncus L. (Juncaceae) in Andalusia (Spain): data on the regional distribution of its species - Romero Zarco, Carlos (Acta Botanica Malacitana, 2010)
Español. Se estudia la distribución en Andalucía de 29 especies del género Juncus utilizando como unidades corológicas las áreas naturales definidas en las floras regionales. Se desestiman las citas bibliográficas anteriores para la región de J. tingitanus Maire & Weiller. Se propone la nueva combinación J. tenageia var. perpusillus (Fern.-Carv. & F. Navarro) Romero Zarco. English. The distribution of 29 species of the genus Juncus were studied in Andalusia using the natural areas defined in regional floras as chorological units. Previous bibliographic records of J. tingitanus Maire & Weiller were discarded. The new combination J. tenageia var. perpusillus (Fern.-Carv. & F. Navarro) Romero Zarco is proposed.